Learning punk through its products: Combining fashion merchandising practices and pedagogy to develop a subculture of resistance. Issue 2 (1st June 2019) - Sklar, Monica; Helfgott, Caroline; Kitchens, Farah
Punk is a lifestyle, ethos and perspective that deals with social unrest and personal discontent. Learning models are applied as framework in this research to contemplate how punk is learned and enacted as a lifestyle by going through daily fashion merchandising and social practices, such as how punks engage with artefacts and the rules of their scene. The punk subculture uses a pedagogy to their fashion production and consumption, employing the garments of their sartorial style with community interactions to create and symbolize their ethos. The community interacts in unision as newcomers to the scene learn from established participants, take in the knowledge available to them, and shift to self-produced ideas to develop their individualized punk ethos. This study used qualitative online surveys, in-person interviews and social media discussions from self-identified punks in the United States and Canada, as well as archival visits to punk-themed collections in order to analyse the experience of individuals who produce, consume and communicate their punk ethos through their garments.